2014
DOI: 10.1136/jmedgenet-2014-102351
|View full text |Cite
|
Sign up to set email alerts
|

SLC39A5mutations interfering with the BMP/TGF-β pathway in non-syndromic high myopia

Abstract: BackgroundHigh myopia, with the characteristic feature of refractive error, is one of the leading causes of blindness worldwide. It has a high heritability, but only a few causative genes have been identified and the pathogenesis is still unclear.MethodsWe used whole genome linkage and exome sequencing to identify the causative mutation in a non-syndromic high myopia family. Direct Sanger sequencing was used to screen the candidate gene in additional sporadic cases or probands. Immunofluorescence was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 38 publications
1
60
0
4
Order By: Relevance
“…Population-based epidemiological investigations found that the disease is associated with environmental risk factors, such as a close reading distance and less outdoor activity (8,9). With the advent of nextgeneration sequencing, a few of disease genes have been discovered in recent years (18)(19)(20)(21)(22)(23)(24). Because myopia is dependent on both genetics and lifestyle and preschool children have less exposure to environmental risks, we designed this study using a special cohort with EOHM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population-based epidemiological investigations found that the disease is associated with environmental risk factors, such as a close reading distance and less outdoor activity (8,9). With the advent of nextgeneration sequencing, a few of disease genes have been discovered in recent years (18)(19)(20)(21)(22)(23)(24). Because myopia is dependent on both genetics and lifestyle and preschool children have less exposure to environmental risks, we designed this study using a special cohort with EOHM.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the identified genetic contributions of the dozens of loci and genes to myopia are very limited. To date, based on pedigree studies with next-generation sequencing, several disease-causing genes have been discovered, including two recessive genes, LRPAP1 (18) and LEPREL1 (19); four dominant genes, ZNF644 (20), SCO2 (21), SLC39A5 (22), and P4HA2 (23); and one X-linked gene, ARR3 (24). However, a large-scale screening of these genes in HM cohorts provided evidence that only a small proportion (<5%) of HM patients harbor mutations in these known genes, which can be attributed to as-yetunidentified causative genes (25).…”
mentioning
confidence: 99%
“…ZIP5 is also expressed during the whole process of eye development, mainly in the sclera and retina (133). Zinc mediated by ZIP5 is likely to be involved in the regulation of Smad protein expression (133). Complete disruption of the Zip5 gene in mice, and intestine-or pancreas-specific disruption of the Zip5 gene in mice, clearly indicates that ZIP5 participates in the control of zinc excretion.…”
Section: E Zip5 (Liv-1 Subfamily)mentioning
confidence: 99%
“…ZIP5 is abundantly expressed in the small intestine and pancreas (83). ZIP5 is also expressed during the whole process of eye development, mainly in the sclera and retina (133). Zinc mediated by ZIP5 is likely to be involved in the regulation of Smad protein expression (133).…”
Section: E Zip5 (Liv-1 Subfamily)mentioning
confidence: 99%
See 1 more Smart Citation